Requirement of two simultaneous environmental signals for activation of Arabidopsis ELIP2 promoter in response to high light, cold, and UV-B stresses - Okechukwu Samson Ezeh; Natsuki Hayami; Kana Mitai; Wasei Kodama; Satoshi Iuchi; Yoshiharu Y. Yamamoto (Plant Signaling & Behavior)
Arabidopsis EARLY LIGH-INDUCIBLE PROTEIN 2 (ELIP2) is a chlorophyll- and carotenoid-binding protein and is involved in photoprotection under stress conditions. Because its expression is induced through high light, cold, or UV-B stressors, its mechanism of induction has been studied. It is known that a functional unit found in the promoter, which is composed of Element B and Element A, is required and sufficient for full activation by these stressors. In this study, the role of each element in the unit was analyzed by introducing weak mutations in each element as synthetic promoters in addition to intensive repeat constructs of each single element. The results suggest that a stressor like cold stress generates two parallel signals in plant cells, and they merge at the promoter region for the activation of ELIP2 expression, which constitutes an “AND” gate and has a potential to realize strong response with high specificity by an environmental trigger.